ChemInform Abstract: Fe3O4@Silica Sulfonic Acid Nanocomposite as a Magnetically Separable Catalyst for the Synthesis of 2‐Arylpyrrolo[2, 3, 4‐kl]acridin‐1(2H)‐ones. Issue 2 (23rd December 2015) - Ghasemzadeh, Mohammad Ali; Mirhosseini‐Eshkevari, Boshra
Abstract: via a one‐pot, three‐component reaction of dimedone, anilines and isatin